PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT. EKA SARI LORENA “ESL EXPRESS” - Christy Elsa Ulita; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research was conducted at PT. Eka Sari Lorena “ESL Express” Pekanbaru, as for the purpose of this study was to determine the effect of system quality, information quality, and service quality to costumer satisfication at PT. Eka Sari Lorena “ESL Express” Pekanbaru. System quality, information quality, and service quality as the independent variable (X1X2X3) while the costumer satisfication as the dependent variable (Y). The problem in this research is the sale of room service of PT. Eka Sari Lorena “ESL Express” fluctuated in the last few years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS. The result of research indicates that for t test, system quality,information quality, and service quality partially have a significant effect on customer satisfication. And the result of F test indicates that system quality, information quality, and service quality simultaneously have a significant effects on customer satisfication. Keywords: System Quality, Information Quality, Service Quality, Customer Satisfication